Comparative Study of the Effect of the Parameters of Sizing Data on Results by the Meshless Methods (MLPG) - Moussaoui, Ahmed; Bouziane, Touria (My University, 2013)
The local Petrov-Galerkin methods (MLPG) have attracted much attention due to their great flexibility in dealing with numerical model in elasticity problems. It is derived from the local weak form (WF) of the equilibrium equations and by inducting the moving last square approach for trial and test functions in (WF) is discussed over local sub-domain. In this paper, we studied the effect of the configuration parameters of the size of the support or quadrature domain, and the effect of the size of the cells with nodes distribution number on the accuracy of the methods. It also presents a comparison of the results for the Shear stress, the deflections and the error in energy
Keywords: MLPG; Meshless Method; Linear Elasticity; Cantilever Plates; Support Domain